1989
DOI: 10.1128/mcb.9.5.2264
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation in vitro of a leukemia virus-induced B-cell lymphoma into macrophages.

Abstract: Cells of the hemopoietic system arise by proliferation and differentiation of progenitor cells. This process begins with multipotential stem ceUls which can self-renew and also undergo progressive differentiation to progenitor cells committed to particular lineages, ultimately yielding mature blood cells (D. Metcalf and M. A. S. Moore, Haematopoietic Cells, 1971). Early commitment of lymphoid progenitors is generally believed to separate the lymphoid lineage from the myeloid and erythroid lineages, whose proge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…Moreover, this model throws some light on the observed conversion from pre-B cell to myeloid cell (21,22 …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, this model throws some light on the observed conversion from pre-B cell to myeloid cell (21,22 …”
Section: Discussionmentioning
confidence: 96%
“…Further evidence for the proximity between the two lineages has come from the in vitro conversion of pre-B leukemia cells into macrophages (22). The existence of a group of nuclear proteins that are highly expressed in both macrophages and pre-B cell lines and whose expression decreases during B-cell differentiation (class C) might be interpreted as corresponding to proteins expressed at a basal level in precursor cells and linked to some specialized macrophage function, thus explaining their induction in macrophages and their repression in plasmocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In the error-prone retroviral system used here, transformation by two of three viral strains (SV8 and 1B1) was primarily caused by dramatic overexpression of Axl rather than through activating mutations, since both viral sublines transmit the intact axl sequence. Activating promoter mutations of the MoMLV-LTR can account for upregulated gene expression and have also been documented to change the host expression speci®city of the retrovirus (Hanecak et al, 1991). The possibility that viral infection induced cellular transformation by insertional mutagenesis is unlikely since the acutely transforming nature of the viral strain was carried with each successive viral passage.…”
Section: Discussionmentioning
confidence: 99%
“…30 This anomalous expression of MyAg on differentiated B-cell leukemia and lymphoma suggest that the pathways of B-lymphoid and myeloid differentiation may be closer than previously appreciated. In fact, some investigators have reported that B-cells can differentiate into macrophages, 31 and that monocytoid cells can generate into plasma cells. 32 In addition, Epstein and colleagues 33 speculated that a multipotent progenitor cell was involved in MM on the basis of the presence of MM cells expressing multilineage markers.…”
Section: Discussionmentioning
confidence: 99%